2020
DOI: 10.1051/0004-6361/201937170
|View full text |Cite
|
Sign up to set email alerts
|

The properties of He IIλ1640 emitters at z ∼  2.5–5 from the VANDELS survey

Abstract: Aims. Strong He ii emission is produced by low-metallicity stellar populations and in this study, we aim to identify and study a sample of He ii λ1640 emitting galaxies at redshifts of z − 2.5 − 5 in the deep VANDELS spectroscopic survey. Methods. We identify a total of 33 Bright He ii emitters (SNR > 2.5) and 17 Faint emitters (SNR < 2.5) in the VANDELS survey. We use the available deep multiwavelength data to study their physical properties. After identifying 7 potential AGN in our sample and discarding them… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 76 publications
2
51
0
Order By: Relevance
“…The fact that the BPASSv2.2 models lie closer to the observed line ratios clearly indicates that increasing the strength of the ionizing continuum at fixed ★ helps to alleviate this problem, and that an insufficiently hard ionizing continuum is likely to be contributing to the discrepancy. Indeed, this conclusion has also frequently been reached with respect to modelling the He emission line in metal-poor starforming galaxies across a large range of redshifts (e.g., Plat et al 2019;Saxena et al 2020). Additionally, the offset may be related to the fact that most photoionization models treat galaxies as single H regions, when in reality the observed spectra are a line luminosityweighted averages of many H regions, each with distinct physical properties.…”
Section: Photoionization Modelsmentioning
confidence: 80%
“…The fact that the BPASSv2.2 models lie closer to the observed line ratios clearly indicates that increasing the strength of the ionizing continuum at fixed ★ helps to alleviate this problem, and that an insufficiently hard ionizing continuum is likely to be contributing to the discrepancy. Indeed, this conclusion has also frequently been reached with respect to modelling the He emission line in metal-poor starforming galaxies across a large range of redshifts (e.g., Plat et al 2019;Saxena et al 2020). Additionally, the offset may be related to the fact that most photoionization models treat galaxies as single H regions, when in reality the observed spectra are a line luminosityweighted averages of many H regions, each with distinct physical properties.…”
Section: Photoionization Modelsmentioning
confidence: 80%
“…Possible sources for such hard radiation are (in addition to Wolf-Rayet stars themselves) population III stars (Schaerer 2003), massive stars undergoing quasi-chemically homogeneous evolution (Kubátová et al 2019), stripped binary stars (Götberg et al 2017), X-ray binaries (Schaerer et al 2019), and radiative shocks (Allen et al 2008). Saxena et al (2020) report EW values of ∼1−4 Å in a sample of He ii 1640-emitting galaxies at redshift 2.5−5.0 (see also Steidel et al 2016;Patrício et al 2016). Slightly larger values (5 to 30 Å) are given by Nanayakkara et al (2019) at redshifts from 2 to 4, while values lower than 1 Å are also reported by Senchyna et al (2017) in nearby galaxies.…”
Section: He II 1640 Emissionmentioning
confidence: 99%
“…As Saxena et al (2020) noted, there is a slight caveat of the stellar metallicity measurement method from Cullen et al (2019) used in their work. With this method, the template fitting used to determine stellar metallicities from features in the rest-frame UV spectra assumes a constant star-formation history.…”
Section: Dependence On Metallicitymentioning
confidence: 99%
“…Rest-frame UV observations of some of these z ∼ 0 metal-poor galaxies have revealed the presence of both He II λ1640 as well as C IV λ1540 emission lines (Berg et al 2019;Senchyna et al 2020), reinforcing the idea of high ionization due to massive, metal-poor stars. The samples of He II emitting galaxies at high redshifts have increased too, primarily using lensing (Patrício et al 2016;Berg et al 2018) and large-area spectroscopic surveys (Cassata et al 2013;Nanayakkara et al 2019;Saxena et al 2020), leading to detections of He II emitting galaxies out to z ∼ 4.…”
mentioning
confidence: 99%
See 1 more Smart Citation